Galloping Control for Iced Conductors Using Tuned Mass Dampers with Fixed Time-Delayed Feedback - Guo Li; Li Li; Peng Zhu (Shock and Vibration)
A tuned mass damper with fixed time-delay feedbacks (TTMD) is first applied to suppress galloping of iced conductors. It is different from general time-delay feedback control, which also connects an added mass to a galloping body and can absorb vibrational energy. The two-degrees-of-freedom model captures the essential mechanical behaviors of iced conductors with TTMD undergoing galloping. The harmonic balance method is then employed to obtain the approximate analytical solutions of the system. Particularly, the expressions of galloping amplitude and angle frequency were obtained. Then the influence regulations of the time-delay parameter T and strength parameter K on galloping control are fully analysed. The results show the added fixed time-delay feedback control can promote the TTMD’s effect, when suitable time-delay parameter T and strength parameter K are chosen. Moreover, the response amplitude and natural frequency change periodically with time-delay parameter T. With strength parameter K increasing, the response amplitude increases or decreases for a fixed value of T and the TTMD’s effect can be enhanced.